Characterization of a protein-bound polysaccharide from Herba Epimedii and its metabolic mechanism in chronic fatigue syndrome. (5th May 2017) - Chi, Aiping; Shen, Zhimei; Zhu, Wenfei; Sun, Yuliang; Kang, Yijiang; Guo, Fei
Abstract: Objectives: Herba Epimedii is one of the famous Traditional Chinese Medicines used to treat the chronic fatigue syndrome (CFS). The polysaccharides are the main active components in H. epimedii. The aim of this study is to discover the therapeutic effect and metabolic mechanism of H. epimedii polysaccharides against CFS. Methods: The polysaccharide conjugates named HEP2-a were isolated from the leaves of H. epimedii using a water extraction method, and the general physicochemical properties of HEP2-a were analysed. In addition, a CFS rat model was established, and then, urinary metabonomic studies were performed using gas chromatography time-of-flight mass spectrometry (GC-TOF-MS) in combination with multivariate statistical analysis. Results: The physicochemical properties revealed that HEP2-a had an average molecular weight of 13.6×10 4  Da and consisted of mannose (4.41%), rhamnose (5.43%), glucose (31.26%), galactose (27.07%), arabinose (23.43%), and galacturonic acid (8.40%). The amino acids in HEP2-a include glutamate, cysteine, leucine, tyrosine, lysine, and histidine. Molecular morphology studies revealed many highly curled spherical particles with diameters of 5–10 µm in solids and 100–200 nm for particles in water. Five metabolites in the HEP2-a group were oppositely and significantly changed compared to the CFS model group. Conclusion: Two metabolic pathways were identified as significant metabolic pathways involved with HEP2-a. The therapeutic effects of HEP2-a on CFS were partially due to the restoration of these disturbed pathways. Graphical abstract: